Description of the Acceptance Level of Free Nutritious Food (MBG) at SDN 50 Ternate City - Fahmilusman Fahmilusman (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
The Free Healthy Meals (MBG) program in elementary schools is an effort to improve the nutritional status and healthy eating habits of school-aged children. This study aims to describe students' acceptance of MBG at SD 50, Ternate City, based on their preferences and food waste. The study used a quantitative descriptive design involving 45 students as respondents. Acceptance data were obtained through visual observation of food waste, which was categorized as <20%, 20–40%, and >40%, then classified into two categories: like and dislike. The results showed that the majority of students left food waste in the low category (<20%), amounting to 32 students (71.1%). Based on the preference grouping, 32 students (71.1%) were categorized as like, while 13 students (28.9%) were categorized as dislike. These findings indicate that the acceptance of MBG among students at SD 50, Ternate City, is good. The results of this study can serve as a basis for school and program administrators to evaluate and develop menus to increase student acceptance of MBG.